FORMULASI DAN EVALUASI SEDIAAN HAND WASH MINYAK SERAI WANGI (Cymbopogon nardus L. Rendle) - Rakhmadhan Niah; Novia Ariani; Dwi Rizki Febrianti (Jurnal Insan Farmasi Indonesia, 2022)
Provision of liquid soap by maximizing the use of natural ingredients as active substances is still not widely developed. One natural ingredient that has been proven to inhibit bacterial growth is citronella oil. Citronella oil can be developed as an active substance for making hand washing soap. The research objective was to formulate and evaluate liquid hand washing soap containing citronella essential oil. The method of this study was to formulate citronella oil soap preparations with a foam forming ratio (CAPB) in formulas 1, 2 and 3. The soap formulation was tested to evaluate the physical quality of the soap preparation. Data analysis was performed using the SPSS method. Based on the results of research on hand wash formulations of citronella essential oil, the formulations that met the test requirements were formulas 2 and 3. However, the most suitable formulations that met the organoleptic and spreadability tests were formulation 3.